Transforming K-12 Education By Blending the Ubuntu Philosophy and Social Justice Principles - Wiafe, Ernestina (My University, 2023)
Considering the highly diverse nature of U.S population, there is no surprise for the calls for a socially just education and a transformative diverse pedagogy in schools seeking to promote a sense of community and belonging. The researcher is of the view that while sections of the population such as Native Americans, People of African Ancestral Origin (Blacks), and Hispanics come from a background of oppression, marginalization, limited opportunities, and exclusion, a blends of ubuntu philosophy and Social Justice principles can be essential to enact K-12 students with values capable of cultivating consciousness about Diversity, Equity, Inclusion, and Belonging (DEIB). • Ubuntu is an ancient African worldview associated with humanness or being humane (ed. Letseka, 2000; Caracciolo & Mungai, 2009 ). • It translates to I am because you are, you are because I am. Ubuntu concerns with ‘I/We’ which are more acceptive of interdependence, as opposed to the ’I/You’ relationships, which assert individualism (Letseka, 2000).
Keywords: Ubuntu Philosophy; Social Justice Education; Collective Fingers; Content Analysis